المحددات الاجتماعية لمهنــة المرأة دراسة ميدانية من وجهة نظر أساتذة جامعة بغداد مجمع الجادريـــة (Journal Of Educational and Psychological Researches, 2012)
The conventional view to women is still in society due to the male domination on society and the social values. Since women and the costumes and women. Since women is not half the society, but half of its potential energy that is capable of working. Giving her the chance to work according to her efficiency and ability and academic achievement is a justice in the distribution of professions between the sexes without discrimination. Women bear the responsibility of correcting the view created by men.The importance of this study comes from knowing the most important social limitations of women work in society which effect on many aspects in her life like choosing a career suiting hers and the range of women working in the university of Baghdad – Jadriya complex towards working women for the increase of the number of working women to contribute to the economic activity starting from the principles of the heavenly religions, specially Islam.The study aims at:• Knowing the social limitations that should determine the profession of women in society.• Knowing the professions which women practiced in history.• Comparing the previous studies with this one.• Shedding light on the importance of the activities of women in working.